Incidence and Survival of Children and Adolescents With Wilms Tumor, United States, 2001–2020 - Andres F. Espinoza; Ekene Onwuka; David A. Siegel; Shifan Dai; Sanjeev A. Vasudevan; Michael E. Scheurer; Philip J. Lupo (Cancer Medicine)
ABSTRACT Background Wilms tumor (WT) is the most common pediatric malignancy of the kidney. Past studies describing WT incidence and survival used surveillance data with < 30% of the US population. We evaluated differences in WT incidence and survival comparing demographic groups and tumor characteristics. Methods We analyzed new cases of WT among patients aged < 20 years at diagnosis by using incidence data from US Cancer Statistics (USCS) for 2003–2020 and 5‐year relative survival (RS) data from the National Program of Cancer Registries (NPCR) for 2001–2019. To assess incidence trends, average annual percent change (AAPC) was calculated by using joinpoint regression. Relative survival (RS) and all‐cause survival were calculated overall and by demographic and clinical variables. Results During 2003–2020, 8218 cases of WT were reported in USCS, which represented an age‐adjusted incidence rate of 5.7 cases per million. Rates were the highest among females (6.3), children aged 0–4 years (17.2), and non‐Hispanic Black patients (7.1). Overall, trends remained stable (AAPC = −0.4, 95% CI: −1.4 to 0.4). Among 7567 cases of WT in NPCR, 5‐year RS was 92.6%. Patients with the lowest survival include the following: those aged 10–19 years (hazard ratio [HR] = 1.65, 95% CI: 1.02–2.65); non‐Hispanic Black patients (HR = 1.39, 95% CI: 1.11–1.76); those with regional stage (HR = 1.93, 95% CI: 1.47–2.54) or distant stage (HR = 5.12, 95% CI: 3.99–6.57); and patients from nonmetropolitan counties (HR = 1.46, 95% CI: 1.09–1.96). Individuals diagnosed during 2011–2019 (HR = 0.64, 95% CI: 0.53–0.77) had higher survival than those diagnosed during 2001–2010. Conclusions The highest WT incidence rates were patients who were female, 0–4 years, and non‐Hispanic Black. Survival improved during the study period; survival differed by race, ethnicity, metropolitan status, and age. Further studies to delineate the causes of these disparities may improve outcomes.